Предмет: Алгебра,
автор: farid72002
Помогите пожалуйста,срочно надо
Преобразуйте в многочлен
(a-2)(a+2)-2a(5-a)
(y-g)^2-3y(y+1)
3(x-4)^2-3x^2
Ответы
Автор ответа:
0
(a-2)(a+2)-2a(5-a)=a^2-4-10a+2a^2=3a^2-10a-4
3(x-4)^2-3x^2=3(x^2-8x+16)-3x^2=3x^2-24x+48-3x^2=-24x+48
3(x-4)^2-3x^2=3(x^2-8x+16)-3x^2=3x^2-24x+48-3x^2=-24x+48
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Обществознание,
автор: katyshovaa
Предмет: Алгебра,
автор: Аноним
Предмет: Химия,
автор: dеniska18
Предмет: Биология,
автор: Korotovskaya